Recent research progress of optical fiber sensors based on D-shaped structure. (1st May 2017) - Ying, Yu; Si, Guang-yuan; Luan, Fang-jun; Xu, Ke; Qi, Yuan-wei; Li, Hong-nan
Abstract: The review summarizes recent studies on D-shaped optical fibers and their recent applications in optical sensors. The configurations and working principles of D-shaped optical fibers are introduced. For each optical fiber sensor, the structure principles and measuring methods are all discussed in detail, with their optimal characteristics and performances being compared. Results from various studies show that it is possible to realize a high-sensitivity optical fiber sensor with a simple structure, good mechanical properties, and strong anti-interference ability. This may be due to the excellent structural design of the D-shaped optical fiber. Finally, key issues and new challenges on the D-shaped optical fiber are discussed. Highlights: The developments of the D-shaped fiber sensor have been reviewed. Optimization methods have been summarized. Different sensing applications have been compared and analyzed. Future research directions have been predicted.